A study on disturbance factors of traffic flow to the communities in Jalan Maran-Gambang (Pekan Gambang), Pahang Darul Makmur - Nor Aisyah, Rumidi (2014)
Traffic flow disruption had been rapidly increase in Malaysia This problem, which causes traffic problems and sometimes vehicles, had lined up (bumper to bumper). Problem in traffic flow occur because of some disturbance factors. Problem of traffic flow disruption during peak hours al*ays occur and posed problem to community and their daily activities. Therefore, this research was conducted to evaluate the traffic flow performance based on link capacity analysis and parking occupancy and to identify the problems faced by the residents which affect to their daily activities. To achieve the objective, a link capacity and parking study was carried out alongside with the distribution of questionnaire to the residents. A straight road of Jalan Maran-Gambang was selected to serve as a study area. From the result it was shown that the occupancy of parking is 83.82%. Thus, it is may cause of traffic congestion because other vehicles need to slow down their vehicles and time delay also will be increase. If more short parking the more it affects the rate of traffic movements. Result also had shown from link capacity analysis. The Level of Service (LOS) of the traffic flow is LOS C and for the growth factor 15% the LOS remain same. From the questionnaire, the result shown that the major factors of traffic flow disruption is heavy vehicles. It can be conclude that the major disturbance factors are from heavy vehicles (91%), the pattern of the parking (87%) and also the narrow road (76%) that may pose danger to community.